2013
DOI: 10.1117/1.jbo.18.1.016003
|View full text |Cite
|
Sign up to set email alerts
|

Dual-tracer background subtraction approach for fluorescent molecular tomography

Abstract: Abstract. Diffuse fluorescence tomography requires high contrast-to-background ratios to accurately reconstruct inclusions of interest. This is a problem when imaging the uptake of fluorescently labeled molecularly targeted tracers in tissue, which can result in high levels of heterogeneously distributed background uptake. We present a dual-tracer background subtraction approach, wherein signal from the uptake of an untargeted tracer is subtracted from targeted tracer signal prior to image reconstruction, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…In Figure S2, it is shown that mouse skin has far less EGFR than the A431 and AsPC-1 tumors but could significantly contribute to the signal in U251 or 9L and as such appropriate receptor concentration thresholds need to be determined. However, non-invasive RCI has recently been demonstrated in mice for lymph node imaging of breast tumor metastases using fluorescence alone (38) and glioma tumors using MRI- and CT-guided fluorescence tomography (39, 40). Additionally, RCI has potential for imaging other primary cancers such as breast tumors (4143) where multiple measurements could be taken over a course antibody therapy to monitor treatment progress.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure S2, it is shown that mouse skin has far less EGFR than the A431 and AsPC-1 tumors but could significantly contribute to the signal in U251 or 9L and as such appropriate receptor concentration thresholds need to be determined. However, non-invasive RCI has recently been demonstrated in mice for lymph node imaging of breast tumor metastases using fluorescence alone (38) and glioma tumors using MRI- and CT-guided fluorescence tomography (39, 40). Additionally, RCI has potential for imaging other primary cancers such as breast tumors (4143) where multiple measurements could be taken over a course antibody therapy to monitor treatment progress.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the uptake of these dyes enables recovery of binding potential, BP, a quantitative parameter proportional to the concentration of receptors available for binding. 1,[4][5][6] With the rise of targeted therapeutic agents in the treatment of cancer, BP is a potentially clinically relevant parameter, which can either inform in regards to the binding affinity of a new targeted drug to a model cancer tumor or be used for receptor concentration estimation of a tumor using a targeted drug of known affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, such a concept was recently applied to FMT (Ref. 7) and showed the improved reconstruction of fluorescence localization. In order to move toward absolute quantification in contrast to relative quantification as presented herein, as well as improved localization, the adaptation of such internal control methods could further enhance multiparameter FMT methods, particularly in regard to longitudinal studies where the measurements at different time points should be quantitatively comparable.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of approaches like this is the creation of internal controls using, e.g., an active and an inactive form of an agent, each labeled with a different fluorochrome. 6,7 In this example, biodistribution and delivery of the agent can be separated by active targeting on the same animal by comparing the images at the two fluorescence channels. Alternatively, different contrast mechanisms can be concurrently studied, e.g., the relative expression of different receptors or the relative concentrations of different types of cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation